The family Oppiidae Grandjean, 1954 (Acari: Oribatida) in the fauna of Vietnam. I. Subfamilies Pulchroppiinae, Oppiellinae, Mystroppiinae, Brachyoppiinae and Arcoppiinae - Manh, Vu Quang; Quyen, Le Thi; Trinh, Dao Duy (Academia Journal of Biology, 2014)
An outline of the classification of the family Oppiidae Grandjean, 1954 (Acari: Oribatida), the identification keys to the subfamilies, genera and species as well as their species recorded in Vietnam are given in the paper. After the classification of Subias and Balogh (1989), in Vietnam, there have been recorded 21 species, belonging to 7 subfamilies: Pulchroppiinae Balogh, 1983; Oppiellinae Seniczak, 1975; Mystroppiinae Balogh, 1983; Brachyoppiinae Subias et Balogh, 1989; Arcoppiinae Balogh, 1983; Oppiinae Grandjean, 1951 and Multioppiinae Balogh, 1983. This part of the paper reports on the first 5 subfamilies with their 11 species recorded in Vietnam: Pulchroppia vietnamica (Balogh et Mahunka, 1967); P. granulata Mahunka, 1988; Oppiela nova (Oudemans, 1902); Striatoppia opuntiseta Balogh et Mahunka, 1968; S. papillata Balogh et Mahunka, 1966; Karenella acuta (Csiszar, 1961); Kokoppia dendricola (Jeleva et Vu, 1987); Arcoppia arcualis (Berlese, 1913); A. baloghi Subias, 1984; A. hammereae Rodriguez et Subias, 1984 and A. longisetosa Balogh, 1982.